To trust or to control: Informal value transfer systems and computational analysis in institutional economics - Claudius Gräbner; Wolfram Elsner; Alex Lascaux (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper illustrates the usefulness of computational methods for the investigation of institutions. As an example, we use a computational agent-based model to study the role of general trust and social control in informal value transfer systems (ITVS). We find that, how and in which timeline general trust and social control interact in order to make ITVS work, become stable and highly effective. The case shows how computational models may help (1) to operationalize institutional theory and to clarify the functioning of institutions, (2) to test the logical consistency of alternative hypotheses about institutions, and (3) to relate institutionalist theory with other paradigms and to practice an interested pluralism.
Keywords: C63; C72; D02; F33; G23; 330; agent-based computational economics; evolutionary-institutional economics; informal value transfer systems; general trust; social control